Potencial antimicrobiano do veneno e ecologia alimentar de Rhinella henseli - Huning, Douglas da Silva (2020)
The population decline of anuran amphibians in different regions of the planet has led to a series of efforts to understand aspects of their ecology and interactions within the community with a view to measures to protect species, as well as to draw attention to their importance for the environment and humanity. We work here with two populations of Rhinella henseli (Lutz, 1934) (Anura: Bufonidae), a species of frog native to southern Brazil, both sampled in the Mata de Pinheiros in southern Atlantic Forest, southern Brazil. We evaluated the antimicrobial potential, chemical composition and spatial variation of the species' venom. We verified, using the agar diffusion method, that the poison inhibited the multiplication of the yeast Candida albicans and reduced the growth of the Staphyococcus saprophyticus bacteria. The composition of the species venom was based on steroidal buffaloids, which varied between the two populations. The R. henseli venom has a composition common to other anurans in the group, and its antimicrobial potential may be related to the buffaloes detected in the species. To deepen the knowledge about the species and to search for relationships between frog poison and its environment, we evaluated the diet of R. henseli, defining its niche range, variation between populations and between climatic seasons. We found that both populations predominantly consume ants of the genus Pachycondyla sp .. We also detected variation in the diet between the cold and hot seasons. The composition of its diet, based on ants, with little spatial variation, indicates that R. henseli consumes the most abundant items in the forest leaf, although we have not analyzed chemically, the species may be using compounds sequestered from the diet in the synthesis of its poison. Thus, the R. henseli venom is composed of steroidal buffaloids whose compounds vary between populations. The venom of the species has bioactivity against C. albicans and S. saprophyticus. Their diet is based on Pachycondyla sp. and the composition of its prey varies between populations and periods of the year